Central Pontine and Extrapontine Myelinolysis: The Great Masquerader—An Autopsy Case Report. (4th March 2014) - Jacob, Sajish; Gupta, Harsh; Nikolic, Dejan; Gundogdu, Betul; Ong, Shirley
Abstract : Central pontine myelinolysis is a demyelinating disorder characterized by the loss of myelin in the center of the basis pontis usually caused by rapid correction of chronic hyponatremia. The clinical features vary depending on the extent of involvement. Demyelination can occur outside the pons as well and diagnosis can be challenging if both pontine and extrapontine areas are involved. We herein report a case of myelinolysis involving pons, lateral geniculate bodies, subependymal region, and spinal cord. To the best of our knowledge, this case represents the second case of spinal cord involvement in osmotic demyelination syndrome and the first case of involvement of thoracic region of spinal cord.